Sekuritisasi Isu Separatisme Patani, Thailand Selatan dalam Perspektif Konstruktivisme - Wulandari, Cintya; Susiatiningsih, Hermini; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The escalation in insurgency by Southern Thailand separatist groups that began with the Arion military raid, the Krue-se and Tak Bai incidents in 2004, promted the Thai government to take securitization action against an ethnational nationalist issue that had not previously been considered a political issue. This research aimed an explanation of the securitization process undertaken by the Thai government to construct the ethnonationalist issue of Southern Thailand as a threat to Thailand's national security. This research uses the securitization theory which is focus in speech act. Speech act is the process of securitization where policy makers (stakeholders) gave an official statement to change the public's opinion on the issue.This research uses qualitative method through library literature data. The results of this study found that the process of securitization of ethno-nationalist issues in South Thailand originated from a non-political issue that became a political issue after being constructed by Thai government officials statements by speech act such as